PERANCANGAN FOTO PREFORM REJECTOR DALAM UPAYA MENGATASI LIMBAH NON-B3 - I Ketut Yogi Swarananda; Putu Oka Sutrisna (Lembaga Penelitian dan Pengabdian Masyarakat (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2023)
The need to use plastic as packaging material for food and beverages still has great opportunities. In the process of making packaging bottles, a machine called blow molding is required. The aim of this research is to design photo rejector preforms for injection blowing tools installed on blow molding machines that must have high strength so that they are able to support the load of the injection tools and mold cavity in an effort to deal with non-b3 waste. The research method uses the Six Sigma method to reduce defects based on the RPN (Risk Priority Number) value. Based on the research results, there are several types of defects that occur in the 2000 ml ASB blow molding machine, namely: runner defects, preform defects, and bottle defects. The 2000 ml defective bottle has the three highest causes of defects, namely: the absence of standards for machine startup with an RPN value of 448, components exceeding the useful life limit with an RPN of 378, and the absence of machine checking standards with an RPN of 336. The total production cost is more efficient at IDR 8.700.000. Thus, the total reduction in non-B3 waste from this innovation in 2022 will be 1.94 tons. This can reduce environmental damage significantly.